2021
DOI: 10.1371/journal.ppat.1009704
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided antibody cocktail for prevention and treatment of COVID-19

Abstract: Development of effective therapeutics for mitigating the COVID-19 pandemic is a pressing global need. Neutralizing antibodies are known to be effective antivirals, as they can be rapidly deployed to prevent disease progression and can accelerate patient recovery without the need for fully developed host immunity. Here, we report the generation and characterization of a series of chimeric antibodies against the receptor-binding domain (RBD) of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…This result suggested that besides RBD-chAb-25, most of our neutralizing Abs might retain activity against these VOCs. Our previous work showed that RBD-chAb-25 and -45 could simultaneously bind to the RBD of SARS-CoV-2 S protein using cryo-EM, and the combination exhibited a synergistic effect compared to single chAbs when used as a prophylactic treatment [ 39 ]. Therefore, we further examined the neutralizing abilities of our six most potent RBD-chAbs toward several SARS-CoV-2 variant pseudoviruses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result suggested that besides RBD-chAb-25, most of our neutralizing Abs might retain activity against these VOCs. Our previous work showed that RBD-chAb-25 and -45 could simultaneously bind to the RBD of SARS-CoV-2 S protein using cryo-EM, and the combination exhibited a synergistic effect compared to single chAbs when used as a prophylactic treatment [ 39 ]. Therefore, we further examined the neutralizing abilities of our six most potent RBD-chAbs toward several SARS-CoV-2 variant pseudoviruses.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that RBD-chAb-45 and -51 share overlapping epitopes according to an ELISA-based competition-binding assay [ 39 ]. In addition, RBD-chAb-15 and -28 have highly similar epitopes, and RBD-chAb-25 has an epitope that partially overlaps with those of RBD-chAb-15 and -28.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-NP mAbs were generated according to previously described procedures [43,44]. Female 4-6-week-old BALB/c mice were immunized with wild-type recombinant NP-His.…”
Section: Generation and Purification Of Mabsmentioning
confidence: 99%